2021
DOI: 10.1007/s00125-021-05605-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between weight change and incidence of cardiovascular disease events and mortality among adults with type 2 diabetes: a systematic review of observational studies and behavioural intervention trials

Abstract: Aims/hypothesis Weight loss is often recommended in the treatment of type 2 diabetes. While evidence has shown that large weight loss may lead to diabetes remission and improvement in cardiovascular risk factors, long-term impacts are unclear. We performed a systematic review of studies of weight loss and other weight changes and incidence of CVD among people with type 2 diabetes. Methods Observational studies of behavioural (non-surgical and non-pharmaceu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
1
13
0
1
Order By: Relevance
“…In addition, our data might include patients with unintentional weight loss, such as malignancy and inflammatory diseases, and this affected the result. However, a previous observational study had reported the relationship of bodyweight loss and improvement of CVD risk factors 23 , and these results are consistent with those of the present study. Furthermore, there were no data based on such a large‐scale clinical practice for Japanese patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, our data might include patients with unintentional weight loss, such as malignancy and inflammatory diseases, and this affected the result. However, a previous observational study had reported the relationship of bodyweight loss and improvement of CVD risk factors 23 , and these results are consistent with those of the present study. Furthermore, there were no data based on such a large‐scale clinical practice for Japanese patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 94%
“…In fact, evidence on the ability for behavioral interventions to reduce the incidence of chronic disease (and related costs) is not compelling. To this point, a recent systematic review concluded that “behavioral interventions targeting weight loss showed no effect on CVD [cardiovascular disease] events” [61]. This calls into question all of the studies suggesting cost‐effectiveness or cost savings from behavioral interventions.…”
Section: Resultsmentioning
confidence: 99%
“…is not compelling. To this point, a recent systematic review concluded that "behavioral interventions targeting weight loss showed no effect on CVD [cardiovascular disease] events" [61].…”
Section: With Funding From the Australian National Health And Medicalmentioning
confidence: 99%
“…[17][18][19][20] Body weight loss of 5% to 10% is considered clinically meaningful and associated with improvements in ORCs. 4,[17][18][19][20][21][22][23][24] Although the association between decreased/increased risk of ORCs with weight loss/gain has been reported previously, [24][25][26][27][28][29] the extent to which the risk of a broad range of ORCs and different degrees of weight loss and weight increase in combination with the BMI before the weight change, is not known.…”
Section: Introductionmentioning
confidence: 99%